Otterboard hydrodynamic performance testing in flume tank and wind tunnel facilities. (1st February 2018) - Mellibovsky, Fernando; Prat, Joana; Notti, Emilio; Sala, Antonello
Abstract: Two pelagic otterboards, previously tested in a wind tunnel, have been tested in a flume tank prior to their analysis in real working conditions in sea trials. This intermediate step aims at providing guidance for sea trial planning and a basis for otter board performance analysis from real campaign data. The doors were rigged in working-like conditions in the flume tank, with onboard-mounted attitude sensors to provide at the same time a noisy environment as expected in sea trials and accurate measurement of all quantities relevant to precise determination of hydrodynamic angles and forces. The trends found in flume tank experiments closely match wind tunnel results, although systematic offset has been observed that can be ascribed to deviations between nominal and real water velocity, due to inhomogeneous velocity distribution in the cross-section. Highlights: We validate a method to exploit door-mounted attitude probes to provide a complete hydrodynamic description of otterboardsin flume tanks and at sea. We show good agreement in the force coefficient trends with accurate wind tunnel results. We identify flume tank water velocity homogeneity as a critical parameter for accuracy.